Marktäckande material som åtgärd för minskat fosforläckage från rasthagar för värphöns - Hellstrand, Ebba (2019)
Today there is a knowledge gap about phosphorus leakage from free range laying hens, and because of that a pilot project is ongoing since 2016 with scientists at The University of Agricultural Sciences (SLU), Research Institutes of Sweden (RISE) and also advisors in order to investigate the nutrient load from free range laying hens. My thesis have been conducted within this project, and I have chosen to focus on phosphorus leakage. My thesis contains three sub studies. The first sub study consist of a literature study, where factors that need to be considered to assess the risk of phosphorus leakage were investigated. The second sub study included analyses of two ground-stabilising materials for paddocks with respect to phosphorus-binding capacity. The third sub study consisted of measuring the concentration of phosphorous in drainage water at organic farms in Östergötland (south of Sweden). I have in all sub studies decided to focus on the area in the paddock with highest animal density, which usually is the area just outside the stable, often gravelled.